Was it a dream or nightmare? A narrative exploration of adult refugee learners’ experiences in a community college - Patricia J. Higgins; Mitsunori Misawa (Adult Education Research Conference, 2021)
Refugees enter the United States seeking a safe place to rebuild their lives after surviving life-threatening situations. In this journey, education is seen as a bridge from instability to self-sufficiency. The purpose of this narrative inquiry was to better understand the experiences of adult refugee learners as they navigate higher education in the United States. The research questions were: How do adult refugee learners’ prior life experiences influence the transition to higher education? How does the intersection of ethnicity and immigration status influence the higher education experience? and What strategies do adult refugee learners employ to navigate higher education?
Keywords: community college; refugee students; adult learning; narrative inquiry